Brain neural mechanisms underlying VR enhanced aerobic exercise for mood enhancement in depressed adolescents - Yao, Shuqi; Wang, Guochen; Peng, Ting; Zhang, Longhai; Ma, Fuhai; Chi, Puyan (Frontiers in Human Neuroscience, 2026)
IntroductionTo compare the immediate effects of a single bout of virtual reality (VR) aerobic exercise versus traditional aerobic exercise on depressive mood in middle-school students and to explore the underlying Electroencephalogram (EEG) microstate and power-spectrum mechanisms.MethodsForty middle-school students were classified into depressed and healthy groups based on the PHQ-9 and completed 15 min of moderate-intensity conventional cycling and VR cycling in a crossover design. Mood was assessed with the Brief Mood Scale (BFS) before and after each intervention, and resting-state EEG was recorded. EEG signals were processed using power spectrum analysis and microstate analysis, and correlation analysis was conducted between BFS questionnaire scores and microstate parameters.ResultsBoth interventions significantly increased vigor and pleasure while reducing depression and lethargy (p < 0.001); VR was superior to traditional cycling in improving vigor, depression, and lethargy (p < 0.01). At baseline, the depressed group showed elevated occurrence and contribution of microstate C with abnormal centroids. After exercise, microstate distributions normalized in both groups; VR specifically reduced microstate C occurrence (p < 0.05), prolonged microstate D duration (p < 0.05), and enhanced B → C and D → B transitions (p < 0.05). Post-VR B → C transition rate correlated negatively with depression (r = −0.462), whereas microstate D occurrence correlated positively with pleasure (r = 0.450). Relative theta, alpha, and beta power decreased after exercise (p < 0.01), without additional VR-mediated power-spectrum gains.ConclusionA single bout of VR-assisted aerobic exercise more effectively enhances immediate mood in middle-school students with depressive symptoms than traditional cycling, likely owing to stronger modulation of microstate dynamics linked to emotion and attention networks and of oscillatory activity in specific frequency bands.